The Political Economy of the Neoliberal Transformation of French Industrial Relations. (May 2016) - Amable, Bruno
The author advances the literature on the role of the state in the decentralization of industrial relations in France by providing a political economic analysis of Right- and Left-backed governments in recent decades. While both have pursued reforms to reduce regulation and to increase labor market flexibility, they have used the state apparatus in different ways to achieve these goals. The Right has reformed labor law by obtaining partial support from employers' associations and unions—the social partners. The Left, by contrast, has relied on decentralized bargaining with the social partners because its political base would not have accepted flexibility-increasing legal reforms. The author examines critical episodes of reform in collective bargaining, unemployment insurance, and employment protection laws to show how the state has intervened in different ways depending on the political identity of the governing coalition.